Alcohol Withdrawal Syndrome - Chandran, Rabindran; Gedam, D Sharad (International Journal of Medical Research and Review, 2016)
Alcohol withdrawal syndrome is a cluster of symptoms occurring when someone detoxes from alcohol. Alcohol dependence is one of the commonest psychiatric disorders, second only to major depression.